Firm Size as Moderator to Non-Linear Leverage-Performance Relation: An Emerging Market Review - Farooq, Umar; Jibran, Ali Qamar (Bina Nusantara University, 2017)
The purpose of this research was to investigate leverage-performance relation with moderating firm size in developing countries like Pakistan. Data were collected from 304 Pakistani non-financial firms for the period of 2005-2013. It is found that overall leverage-performance relation is negative for all types of firms. However,such losses are more prominent for small size firms. Results also show that the leverage-performance relation is nonlinear for medium and large size firms. However, these firms are not targeting optimal level and overleveraging that ultimately decrease their profits. So, financial managers of small size firms should avoid debt financing while for large and medium size firms, managers need to adjust their debt ratio to its optimal level.